Adaptation of the five-factor BFI-10 personality screening questionnaire and testing of its diagnostic properties on the example of drug users - О. О. Serdiuk; В. О. Bazyma (Law and Safety)
Extended annotation. The large number of questions from the most common and cited in the scientific literature questionnaires of the "Big Five" makes them unsuitable for surveys of large samples of poorly motivated respondents. It is described the process of adaptation, validation and diagnostic properties of the five-factor BFI-10 Express Diagnostic Screening Questionnaire, which contains only 10 questions and has shown high reliability in large comparative cross-cultural studies using a web methodology. Validation was performed by filling in parallel forms of the 5PFQ questionnaire for 75 questions (validated version of A.B. Khromov, N = 2492), LBP questionnaire for 25 questions (validated version of L.F. Burlachuk and D.K. Korolev, N = 246) and questionnaire BFI-10. The validation of the BFI-10 has showed that our adapted version of the questionnaire measured the same constructs as the 5PFQ and BFL questionnaires. There is a positive correlation between the total values of the scales of all three questionnaires of the "big five", significant at the level of p <0.01. The highest values of the linear correlation coefficient of the BFI-10 scales are observed for factors "N" - neuroticism (BFL r = 0.620, 5PFQ r = 0.466) and "E" - extraversion (BFL r = 0.688, 5PFQ r = 0.441). The internal consistency characteristics of the 5PFQ, BFL, and BFI-10 questionnaire scales show that the Cronbach's alpha is increased when BFI-10 questions are added to the original 5PFQ and BFL scales. For BFL and BFI-10, Cronbach's alpha ranges from 0.64 to 0.85. For 5PFQ and BFI-10, Cronbach's alpha ranges from 0.76 to 0.88. The BFI-10 adapted variant has showed its diagnostic applicability in a study of drug and non-drug users (N = 4723). The results of the comparison of the average values of the BFI-10 scales (t-test) show that there are statistically significant differences between young people who used and did not use drugs in the 12 months before the survey. The greatest diagnostic significance has been shown by factor "C" - consciousness (t = -8,504; p <0,01). Statistically significant differences have not been detected only by factor "E" (extraversion). Thus, young people who have confessed to drug use can be described as less conscious (responsible), more conflicted (hostile), more neurotic, but also more creative and prone to experimenting and gaining new experiences. The obtained results prove that the proposed adaptation of BFI-10 meets the criteria of diagnostic reliability and validity, and can be recommended for express diagnosis of personality in terms of mass sample surveys and express individual screening of personality traits in the Ukrainian-speaking environment.